Being in-sync: A multimodal framework on the emotional and cognitive synchronization of collaborative learners - Aoyama Lawrence, Lena; Weinberger, Armin (Frontiers in Education, 2022)
Collaborative learners share an experience when focusing on a task together and coevally influence each other’s emotions and motivations. Continuous emotional synchronization relates to how learners co-regulate their cognitive resources, especially regarding their joint attention and transactive discourse. “Being in-sync” then refers to multiple emotional and cognitive group states and processes, raising the question: to what extent and when is being in-sync beneficial and when is it not? In this article, we propose a framework of multi-modal learning analytics addressing synchronization of collaborative learners across emotional and cognitive dimensions and different modalities. To exemplify this framework and approach the question of how emotions and cognitions intertwine in collaborative learning, we present contrasting cases of learners in a tabletop environment that have or have not been instructed to coordinate their gaze. Qualitative analysis of multimodal data incorporating eye-tracking and electrodermal sensors shows that gaze instruction facilitated being emotionally, cognitively, and behaviorally “in-sync” during the peer collaboration. Identifying and analyzing moments of shared emotional shifts shows how learners are establishing shared understanding regarding both the learning task as well as the relationship among them when they are emotionally “in-sync”.